Đề xuất quy trình thiết kế kế hoạch bài dạy song ngữ Anh - Việt môn Khoa học lớp 5 - Trịnh Thị Hiệp, Trịnh Thị Hiệp; Phan Thị Hồng, The (Tạp chí Giáo dục, 2026)
In the context of implementing the Project to make English the second language in schools during the 2025-2035 period, designing bilingual English-Vietnamese lesson plans in primary schools is an urgent requirement to integrate the development of subject-specific competencies and foreign language skills for students. However, research on the process of designing bilingual lesson plans for Science in primary schools is limited. This paper uses a theoretical research method combined with content analysis to build a scientific basis, thereby proposing a system of principles and a process for designing bilingual English-Vietnamese lesson plans for Science in grade 5. The proposed process is illustrated through the lesson plan for the lesson “Human Impact and Some Measures to Protect the Environment” (Science 5). The results of this paper contribute to supplementing the theoretical basis for designing bilingual lesson plans, and provide reference materials for teachers in the process of implementing bilingual teaching and carrying out the Project to make English a second language in schools.